Metformin Had Potential to Increase Endocan Levels in STZ-Induced Diabetic Mice - Elmira Zolali; Sevda Shayesteh; Reza Rahbarghazi; Haleh Vaez; Hamid Reza Heidari; Alireza Garjani (Tabriz University of Medical Sciences, 2020)
Background: Type 2 diabetes mellitus is a chronic metabolic disorder with prominent vascular injuries. In this condition, the levels of multiple pro- and anti-angiogenic factors have been shown to change. This study aimed to investigate the possible effect of metformin on pro-angiogenic factor, endocan levels, via the modulation of p-AMPK/AMPK axis in diabetic mice. Methods: Mice were randomly assigned to one of 4 groups (n=6): Control (normal saline) and the diabetic group was injected streptozotocin and two groups were given 50 and 100 mg/kg metformin orally, once daily for two weeks after diabetes induction. Endocan protein levels were detected in the liver and kidneys by ELISA and immunofluorescence analysis. Phosphorylation of AMPK was assessed using western blotting. Histological examination was performed to follow the metformin effect on Von Willebrand factor expression and diabetes-related pathologies. Results: ELISA assay showed an elevated levels of endocan in the renal and hepatic tissues of diabetic mice following treatment with metformin (p<0.05). Immunofluorescence and immunohistochemistry examination of kidneys showed that the increase of endocan protein coincided with the promotion of vWF factors in mice treated with metformin (p<0.05). We did not find endocan factor in hepatic tissue of diabetic mice pre- and post-treatment with metformin. Western blotting confirmed the phosphorylation of AMPK by metformin in kidneys (p<0.05), but these changes did not reach statistically significant levels in hepatic tissues (p>0.05). Conclusion: Metformin could change the endocan levels during diabetic condition possibly by the modulation of p-AMPK/AMPK axis.